A quasi-experimental study of fresh oxygen flow on patients’ oxygen reserve during mask-assisted ventilation under general anesthesia induction - Shi, Yubo; Jin, Ying; Song, Jianli; Shi, Jingfeng; Liu, Xiaoying; Zhao, Guoqing; Su, Zhenbo (Frontiers in Medicine, 2023)
To compare the effect of different amounts of fresh oxygen flow on oxygen reserve in patients undergoing general anesthesia.Methods: Seventy-two patients were enrolled in this quasi-experimental study.Patients were randomly divided into experimental groups with a fresh oxygen flow of 1L/min, 2L/min, 4L/min, and 8L/min (denoted as G1, G2, G3, and G4, respectively) for 2 minutes of mask-assisted ventilation. Safe apnea time (SAT) was the primary endpoint; SAT was defined as the time from the cessation of ventilation to the time the patient's pulse oxygen saturation (SpO2) decreased to 90%. Ventilation indicators such as end-tidal oxygen concentration (EtO2), end-tidal carbon dioxide partial pressure (EtCO2), SpO2, and carbon dioxide (CO2) elimination amount, during mask-assisted ventilation, were the secondary endpoints.The SAT of G1, G2, G3, and G4 were 305.1±97.0s, 315±112.5s, 381.3±118.6s, and 359±104.4s, respectively (P>0.05). The EtO2 after 2 minutes of mask-assisted ventilation in groups G1, G2, G3, and G4 were 69.7±8.8%, 75.2±5.0%, 82.5±3.3%, and 86.8±1.5%, respectively (P<0.05). Also, there was a moderate positive correlation between the fresh oxygen flow and EtO2 (correlation coefficient r=0.52, 95% CI 0.31-0.67, P<0.0001). The CO2 elimination in the G1 and G2 groups was greater than that in the G4 group (P<0.05). There was no significant difference in other indicators among the groups (all P>0.05).The amount of fresh oxygen flow during mask-assisted ventilation was positively correlated with EtO2. Also, even though there was no significant difference, 3 the patients' oxygen reserves increased with the increase in fresh oxygen flow.